75.3k views
1 vote
Please answer correctly!!!!

Please answer correctly!!!!-example-1
User Chun
by
5.2k points

1 Answer

2 votes

Answer:

(x+3+5i) (x+3-5i) =x^2 +6x+34

(x-4i) (x+4i) = x^2 +16

(x-6+i) (x-6-i) = x^2 -12x+37

Explanation:

(x+3+5i) (x+3-5i)

Let m = x+3

(m+5i) (m-5i)

FOIL (first outer inner last)

Remember i^2 = -1

m^2 -5mi + 5mi -25i^2 = m^2 -25(-1) = m^2 +25

What is m^2 = (x+3)^2

FOIL = x^2 +3x+3x+9 = x^2 +6x+9

Replace m^2 with x^2 +6x+9

(x+3+5i) (x+3-5i) = x^2 +6x+9+25

= x^2 +6x+34


(x-4i) (x+4i) =

FOIL = x^2 +4ix -4ix -16i^2 = x^2 -16(-1) = x^2 +16


(x-6+i) (x-6-i)

Let m = x-6

(m+i) (m-i)

m^2 -mi +mi -i^2

m^2 - (-1)

m^2+1

What m^2

(x-6) ^2 = x^2 -6x-6x+36 = x^2 -12x+36

(x-6+i) (x-6-i) = m^2 +1 =x^2 -12x+36 +1 = x^2 -12x+37

User Malice
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.